1993
DOI: 10.1007/bf02600138
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and preventability of adverse drug events in hospitalized adults

Abstract: The authors conclude that ADEs are not infrequent, often preventable, and usually caused by physician decisions. In this study, solicited reporting by nurses and pharmacists was inferior to chart review for identifying ADEs, but was effective for identifying potential ADEs. Optimal prevention strategies should cover many types of drugs and target physicians' ordering practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
225
0
17

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 318 publications
(248 citation statements)
references
References 17 publications
6
225
0
17
Order By: Relevance
“…Studies have shown that age, gender, co morbidity, number of drugs, and length of hospital stay are significant risk factors for development of ADRs [36,[39][40][41][42][43][44]. Our study revealed polypharmacy and multiple disease state as the most prevalent predisposing factors in patients who developed ADRs.…”
Section: Discussionmentioning
confidence: 52%
“…Studies have shown that age, gender, co morbidity, number of drugs, and length of hospital stay are significant risk factors for development of ADRs [36,[39][40][41][42][43][44]. Our study revealed polypharmacy and multiple disease state as the most prevalent predisposing factors in patients who developed ADRs.…”
Section: Discussionmentioning
confidence: 52%
“…The first group, instruments using only a definition of preventability, included three instruments (8,18,19) (Table II, Figure 2). All three instruments shared the same preventability categories and no specific criteria for determining the type of a preventability category, apart from the definition for preventability, were mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown age, gender, co morbidity, number of drugs, and length of stay in the hospital as significant risk factors for development of ADRs. [27][28][29] Our study revealed polypharmacy, multiple disease state and unnecessary use of antibacterial agents as the most prevalent predisposing factors in patients who developed ADRs. Since many of the reports were from medicine department where in usually the patients have multiple co morbidities and hence polypharmacy contributed to the high percentage of reports with these factors as predisposing ones in our study.…”
Section: -25mentioning
confidence: 95%